Field notes contributed by Peter C. Petersen, fall 1993 - Petersen, Peter C.et al (1993)
Fall report of birds and locations contributed by Peter C. Petersen. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1993. Plustek - flatbed